2017
DOI: 10.1007/s11892-017-0836-9
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Maternal and Infant Microbiome: What Is the Role of Diabetes and Obesity in Pregnancy?

Abstract: Purpose of Review The purpose of this review is to summarize the evidence on whether diabetes, obesity, and related metabolic derangements during pregnancy are associated with the maternal and infant microbiomes, and to identify gaps in the literature and offer guidance on future research on this topic. Recent Findings We found circumstantial evidence from four observational studies that the maternal gut microbiome was associated with either pre-pregnancy body mass index, gestational weight gain, gestational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 75 publications
(85 reference statements)
1
14
0
Order By: Relevance
“…Likewise, intestinal microbiota imbalance leads to inflammation and blood glucose disorders during pregnancy, which may be caused by decreased short‐chain fatty acids, disregulated secretion of related hormones, and decreased tight junctions between intestinal epithelial cells (Singh et al . 2017). Indeed, the composition of intestinal microbiota in the offspring of mothers with different physical conditions (e.g., malnutrition or overnutrition during or after pregnancy) also varies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, intestinal microbiota imbalance leads to inflammation and blood glucose disorders during pregnancy, which may be caused by decreased short‐chain fatty acids, disregulated secretion of related hormones, and decreased tight junctions between intestinal epithelial cells (Singh et al . 2017). Indeed, the composition of intestinal microbiota in the offspring of mothers with different physical conditions (e.g., malnutrition or overnutrition during or after pregnancy) also varies.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of Desulfovibrio , Bacteroides , and Methanobrevibacter have been reported in obese subjects [ 30 , 34 , 35 , 57 ]. Few studies have reported differences in microbiota composition during pregnancy and the influence of pre-BMI and weight gain [ 13 , 46 , 58 ]. Recent studies have revealed the importance of the maternal microbial environment in infants’ health both early and later in life, suggesting that the transfer of the altered gut microbiota from obese pregnant women to their infants may lead to metabolic disorders [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal weight variables represented a special case, with multiple potential confounding variables 15,31,32,35,5153 . GWG would ideally be classified as normal, inadequate, or excessive according to maternal pre-pregnancy BMI and estimated gestational age of delivery, according to Institute of Medicine guidelines 54 .…”
Section: Methodsmentioning
confidence: 99%